The concept of mechanism from a realist approach: a scoping review to facilitate its operationalization in public health program evaluation. (December 2015) - Lacouture, Anthony; Breton, Eric; Guichard, Anne; Ridde, Valéry
Abstract Background Public health interventions are complex by nature, and their evaluation requires unpacking their intervention logic and their interactions with open social systems. By focusing on the interrelationships between context, mechanism, and outcome, Pawson and Tilley's realist approach appears a promising innovation for public health-related evaluation works. However, and as expected of any methodological innovation, this approach is being constructed gradually by answering the multiple challenges to its operationalization that fall in its path. One of these challenges, users of this approach agree on, is the necessity of clarifying its key concept of mechanism. Method We first collected the definitions of mechanism from published works of Pawson and colleagues. Secondly, a scoping review was conducted to identify the ones quoted by users of the realist approach for evaluating public health interventions (1997–2012). We then appraised the clarity and precision of this concept against the three dimensions defined by Daigneault and Jacobs "term, sense and referent." Results Of the 2344 documents identified in the scoping review, 49 documents were included. Term: Users of the realist approach use adjectives qualifying the term mechanism that were not specifically endorsed by Pawson and colleagues. Sense: None of the attributes stated by Pawson and colleagues has been listed in all of the documents analyzed, and some contributions clarified its attributes. Referent: The concept of mechanism within a realist approach can be ascribed to theory-based evaluation, complex social interventions, and critical realism. Conclusion This review led us to reconsider the concept of mechanism within the realist approach by confronting the theoretical stance of its proponents to the practical one of its users. This resulted in a clearer, more precise definition of the concept of mechanism which may in turn trigger further improvements in the way the realist approach is applied in evaluative practice in public health and potentially beyond. A mechanism is hidden but real, is an element of reasoning and reactions of agents in regard to the resources available in a given context to bring about changes through the implementation of an intervention, and evolves within an open space-time and social system of relationships.